Bovine papillomatosis: First detection of bovine papillomavirus types 6, 7, 8, 10 and 12 in Italian cattle herds. (April 2016) - Savini, F.; Mancini, S.; Gallina, L.; Donati, G.; Casà, G.; Peli, A.; Scagliarini, A.
Highlights: Nine different BPVs were detected in bovine proliferative lesions by PCR and RCA. We report the first identification of BPV types, 6, 7, 8, 10 and 12 in Italy. The majority of samples harbored different types co-infections. One clinically diagnosed papilloma lesion tested positive for parapoxvirus. Abstract: Limited information about the distribution of different bovine papillomavirus (BPV) types in Italy is available; therefore, this study aimed to investigate the presence of BPVs in bovine lesions in the Emilia Romagna region. Sixty-four proliferative lesions were collected between december 2011 and december 2014, and subsequently analysed by qualitative PCR with genus- and type-specific primer pairs, as well as rolling circle amplification (RCA). The results demonstrated, for the first time in Italy, the presence of BPV 6, 7, 8, 10 and 12 and also types previously described elsewhere. In addition, the high prevalence of viral co-infections in this sample set provides new information about viral tropism.